Big Data Analytics and Machine Learning: Transforming Fixed Income Investment Strategies - Purshotam S Yadav (North American Journal of Engineering Research, 2021)
The current paper reviews how big data analytics and machine learning are transforming the fixed income investing strategy. Exponential growth in volume, velocity, and variety of financial data is changing traditional methods for investing [14]. In particular, we investigate how big data techniques and machine learning algorithms enhance the market analysis, risk assessment, and decision-making processes in fixed income markets. Our research indicates that the application of such advanced technologies helps create better investment decisions, improved portfolio performance, and enhanced risk management within fixed-income investments.